8 lives of a century-old trickster : a novel - Lee, Mirinae (New York, NY : Harper, an imprint of HarperCollins Publishers, 2023)
"Life near the North Korean border is a zero-sum game, an ongoing battle in which you either win or you lose. This dangerous, shadowed netherworld is home to an unforgettable woman known only as the "trickster." Inspired by the story of Lee's great aunt, one of the oldest women to escape alone from North Korea, 8 Lives of a Century Old Trickster consists of eight dark and spellbinding chapters that follow this remarkable character and her family as they struggle to survive during the most turbulent times of modern Korean history. Mirinae Lee's trickster is a shapeshifter--throughout the course of these interconnected chapters she is a slave, an escape artist, a murderer, a terrorist, a spy, a lover, and a mother--a woman who must often choose the unthinkable to survive war and conquest in Korea. Her story is a beguiling, complex tale of love and survival that will keep you riveted--and speculating--until the very end thanks to Lee's brilliant talent for sleight of hand. A fascinating look at survival, trauma, and family, 8 Lives of a Century-Old Trickster is an incredible literary debut from a bright new talent."--
"Slave. Escape artist. Murderer. Terrorist. Spy. Lover. Mother."--Cover.
Keywords: Survival -- Fiction; Nursing homes -- Fiction; Retirement communities -- Fiction; Older people -- Fiction; World War, 1939-1945 -- Fiction; Korean War, 1950-1953 -- Fiction; Deception -- Fiction; Tricksters -- Fiction; Cold War -- Fiction; Betrayal -- Fiction; War fiction